Limb-threatening compartment syndrome: A rare complication of dengue fever - Kamisan, Saiful Azlan; Kow, Ren Yi; Mor Japar Khan, Ed Simor Khan; Ibrahim, sa'adon (International Medical University, Malaysia., 2018)
Dengue fever, a common mosquito-borne disease in Malaysia, has a wide range of clinical presentations. Dengue shock syndrome, a potentially fatal complication of dengue, is associated with derangement of numerous haematologic markers. A compromised coagulation profle, coupled with a traumatic incident may lead to a serious haemorrhagic complication. We present a rare complication of acute compartment syndrome of the right upper limb in a 17- year-old gentleman who was admitted for decompensated dengue shock syndrome after an unsuccessful attempt of venous cannulation. An emergency fasciotomy was performed and the right upper limb was salvaged albeit with ulnar nerve and radial nerve palsy.